2016
DOI: 10.1186/s13047-016-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of percutaneous flexor tenotomies for the management and prevention of recurrence of diabetic toe ulcers: a systematic review

Abstract: BackgroundDiabetic toe ulcers are a potentially devastating complication of diabetes. In recent years, the percutaneous flexor tenotomy procedure for the correction of flexible claw and hammer-toe contraction deformities has been proposed as a safe and effective technique for facilitating the healing of toe-deformity related diabetic ulcers. The aim of this review is to critically appraise the evidence for the effectiveness of this surgical procedure in achieving ulcer healing, prevention of re-ulceration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…There is no consensus regarding terminology of ulcers appearing after an initial ulcer has healed. In the literature these ulcers are termed recurrent ulcer, reulceration, new ulcer, and transfer ulcer . Often there is no definition of ulcer recurrence at all .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus regarding terminology of ulcers appearing after an initial ulcer has healed. In the literature these ulcers are termed recurrent ulcer, reulceration, new ulcer, and transfer ulcer . Often there is no definition of ulcer recurrence at all .…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited number of studies regarding development of new ulcers following healing of a plantar forefoot ulcer, and with no uniform definitions of recurrent and other new ulcers …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent systematic reviews were identified on the efficacy of digital flexor tenotomy on DFU outcomes . Both reviews identified the same five noncontrolled studies and one of the reviews identified a sixth noncontrolled study .…”
Section: Recommendationsmentioning
confidence: 99%
“…99 In summary, there is some evidence to support surgical vs non- Two recent systematic reviews were identified on the efficacy of digital flexor tenotomy on DFU outcomes. 107,108 Both reviews identified the same five noncontrolled studies [109][110][111][112][113] and one of the reviews identified a sixth noncontrolled study. 114 The larger systematic review reported an overall healing rate of 97% in a mean 29.5 days.…”
Section: Other Offloading Techniquesmentioning
confidence: 99%